Effective Strategies for the Implementation of ICT in the Classroom for Teaching History and Philosophy (Journal of Namibian Studies : History Politics Culture, 2023)
A documentary review was carried out on the production and publication of research papers related to the study of ICT variables and Pedagogical Strategies. The purpose of the bibliometric analysis proposed in this document was to know the main characteristics of the volume of publications registered in the Scopus database during the period 2017-2022, achieving the identification of 162 publications. The information provided by this platform was organized through graphs and figures categorizing the information by Year of Publication, Country of Origin, Area of Knowledge and Type of Publication. Once these characteristics have been described, the position of different authors towards the proposed theme is referenced through a qualitative analysis. Among the main findings made through this research, it is found that Spain, with 35 publications, was the country with the highest scientific production registered in the name of authors affiliated with institutions of that nation. The Area of Knowledge that made the greatest contribution to the construction of bibliographic material referring to the study of Pedagogical Strategies based on ICT and Education, was Social Sciences  with 119 published documents, and the Type of Publication most used during the period indicated above were Journal Articles with 58% of the total scientific production.